The era of genetic testing; from imagination to practicability in Pakistan - Iqbal, Waheed (International Journal of Pathology, 2024)
Genetic testing offers important insights about an individual’s genetic composition, it has emerged as a potent technology that has the potential to completely transform healthcare. This emerging field has potential applications in disease risk assessment, targeted therapies, and personalized medicine. But the quick development of genetic testing also brings up important moral, legal, and societal issues that need to be carefully thought through.1 The ability of genetic testing to determine a person’s susceptibility to specific diseases is among its most important advantages. Healthcare practitioners can learn a great deal about a patient’s risk of getting certain ailments by examining their DNA. This information enables them to take preventive steps to reduce the patient’s risk. Genetic testing can also help doctors make better treatment options by allowing them to customize medications based on a patient’s genetic profile. This can maximize positive outcomes and reduce negative ones.2